Resultatives and dynamic semantics - Bende-Farkas, Ágnes (Proceedings of the Amsterdam Colloquium, 2007)
This paper intends to make three related points concerning resultative constructions. 1. On the basis of Hungarian data it is argued that out of three possible strategies, the method proposed in Kratzer 2004 is preferable. The case endings that mark Hungarian resultatives can be taken as the overt counterparts of the covert morphemes proposed in Kratzer 2004. These morphemes are taken to introduce causal information and to hold the resultative construction together. 2. On the basis of data from Russian and Hungarian it is argued that prefixes and particles are to be analysed with the same tools as nominal result predicates, adjectives, nouns or PPs. 3. It is argued that the best method of semantic composition for resultatives involves dynamic semantics with asymmetric merge (Muskens 1996).